Anxiety Specific Response and Contribution of Active Hippocampal Neural Stem Cells to Chronic Pain Through Wnt/β-Catenin Signaling in Mice - Zhao, Youyi; Zhang, Li; Wang, Mengmeng; Yu, Jianping; Yang, Jiping; Liu, Aidong; Yao, Han; Liu, Xinyu; Shen, Yahui; Guo, Baolin; Wang, Yazhou; Wu, Shengxi (Frontiers in Molecular Neuroscience, 2018)
Chronic pain usually results in persistent anxiety, which worsens the life quality of patients and complicates the treatment of pain. Hippocampus is one of the few brain regions in many mammalians species which harbors adult neural stem cells (NSCs), and plays a key role in the development and maintenance of chronic anxiety. Recent studies have suggested a potential involvement of hippocampal neurogenesis in modulating chronic pain. Whether and how hippocampal NSCs are involved in the pain-associated anxiety remains unclear. Here, we report that mice suffering persistent neuropathic pain showed a quick reduction of active NSCs in the ventral dentate gyrus (vDG), which was followed by the decrease of neurogenesis and appearance of anxiety. Wnt/β-catenin signaling, a key pathway in sustaining the active status of NSCs was suppressed in the vDG of mice suffering chronic pain. Depleting β-catenin by inducible Nestin-Cre significantly reduced the number of active NSCs and facilitated anxiety development, while expressing stabilized β-catenin amplified active NSCs and alleviated anxiety, indicating that Wnt activated NSCs is required for anxiety development under chronic pain. Treatment with Fluoxetine, the most widely used anxiolytic in clinic, significantly increased the proliferation of active NSCs and enhanced Wnt signaling. Interestingly, both β-catenin manipulation and Fluoxetine treatment had no significant effects on the pain thresholds. Therefore, our data demonstrated an anxiety-specific response and contribution of activated NSCs to chronic pain through Wnt/β-catenin signaling, which may be targeted for treating chronic pain- or other diseases-associated anxiety.